HUMAN RIGHTS PROTECTION: Essay to suggest a popular, liberating and militant proposal - Carbonari, Paulo César (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2023)
The article reflects on the proposal to build human rights protection from a popular, liberation and militant perspective. These three qualities complement each other in the sense of offering conditions for protection to occur in conjunction with popular organizational processes, particularly taking into account the care and protection of human rights defenders. The article is organized with a brief analysis of contexts, a debate on vulnerability and violation, assumptions for protective action, a comment on the meaning of protective action in human rights and, finally, a summary of the meaning of popular protection.